Wady wrodzoneRoss operation – risk factors for autograft dilatation. Single centre experience - Siudalska, Hanna; Kuśmierczyk, Beata; Hoffman, Piotr; Barańska, Katarzyna; Różański, Jacek (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2008)
Background: The Ross procedure is considered an excellent alternative for children and selected adult patients requiring elective aortic valve replacement. Although the pulmonary autograft is ideal when it comes to haemodynamics, does not require anticoagulation and has low thromboembolism risk, concern regarding autograft and pulmonary homograft longevity has appeared. In connection with this, we decided to sum up our 14 years of experience. Material and Methods: Between 1994 and 2005, 77 patients (male – 50, female – 27) underwent the Ross operation in the Institute of Cardiology in Warsaw using root replacement technique. Mean age was 24.5±11.1 years. Mean follow-up was 6.7±2.7 years. Sex, age at the operation, bicuspid aortic valve, preoperative interventions, preoperative aorta dilatation, preoperative diagnosis, and postoperative hypertension as a potential risk factor for autograft dilatation were studied. Results: Hospital mortality was 2.5% (n=2). During follow-up 2 patients died (2.5%). Fourteen-year survival was 94.8%. Pulmonary autograft reoperations were required in 5 patients, in 4 because of neo-aortic root dilatation, in 1 because of infective endocarditis. Over time 4 patients required pulmonary homograft reoperation, and 2 patients required replacement of both the pulmonary autograft and allograft. Freedom from autograft reoperation was 91.9 %. Freedom from homograft reoperation was 92.2%. Except for time, no risk factors for autograft dilatation were detected. Conclusions: Although the Ross operation resulted in excellent survival and an acceptable reoperation rate, over time a worrisome increase in reoperation rate is observed. Given the progressive autograft dilatation, careful follow-up of these patients is warranted.